Aerodynamic Investigation of Blended Wing Body Configuration - MV, Midhun; Mondal, Partha; Karn, Pawan Kumar; Kumar, Priyank (Defence Science Journal, 2023)
A blended wing body (BWB) configuration is an unconventional aircraft design in which the wing and fuselage are blended to form an aircraft. This design concept has inherent higher aerodynamic efficiency, environmental benefits and capacities. These advantages make the BWB configuration a feasible concept for commercial transport aircraft. In the present work, a 3-D BWB model is designed in SolidWorks and fabricated using a 3D printer. The numerical and experimental analyses are carried out with this BWB geometry. Aerodynamic characteristics and flow features obtained from the open-source CFD software OpenFOAM have been studied, analyzed, and compared with the wind tunnel results. Experimental and computational data compare well and the present BWB can operate at a high angle of attack. The coefficient of lift (CL) increases with AoA up to 45º. The CL starts decreasing beyond this AoA, and the present BWB geometry stalls at around AoA = 45º. The coefficient of drag (CD) increases with the increase in AoA due to the spreading of the separated region over the geometry. Lift/Drag (L/D) variation with AoA is also studied to find the optimum flight configuration of the present BWB geometry. Sectional pressure distribution at different spanwise locations, velocity contours, pathlines, surface limiting streamlines and tuft flow visualization are also presented to investigate the flow. The studies investigate the aerodynamics, flow field and optimal flight configuration for cruising a BWB geometry.